2015
DOI: 10.1098/rspb.2015.1001
|View full text |Cite
|
Sign up to set email alerts
|

Pervasive and strong effects of plants on soil chemistry: a meta-analysis of individual plant ‘Zinke’ effects

Abstract: Plant species leave a chemical signature in the soils below them, generating fine-scale spatial variation that drives ecological processes. Since the publication of a seminal paper on plant-mediated soil heterogeneity by Paul Zinke in 1962, a robust literature has developed examining effects of individual plants on their local environments (individual plant effects). Here, we synthesize this work using meta-analysis to show that plant effects are strong and pervasive across ecosystems on six continents. Overal… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
87
0
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(93 citation statements)
references
References 46 publications
1
87
0
1
Order By: Relevance
“…), however, our work shows that removing environmental influences may exaggerate the importance of plant host influence on soil microbial community composition. For example, plants may cultivate their own host‐specific pathogens (Packer & Clay, ), but they also modify local soil environments through litter or root exudates (Waring et al., ) in ways that could also suppress the activity of pathogens. Similarly, even though plants may prefer particular mutualists (Kiers et al.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…), however, our work shows that removing environmental influences may exaggerate the importance of plant host influence on soil microbial community composition. For example, plants may cultivate their own host‐specific pathogens (Packer & Clay, ), but they also modify local soil environments through litter or root exudates (Waring et al., ) in ways that could also suppress the activity of pathogens. Similarly, even though plants may prefer particular mutualists (Kiers et al.…”
Section: Discussionmentioning
confidence: 99%
“…Other studies found that fungal saprotroph community composition was linked to dominant forest trees (Urbanova et al., ) and plant traits such as leaf nitrogen content (Nguyen, Williams, et al., ). Direct effects of plant identity, such as root exudates (Haichar et al., ) and indirect effects of plant identity on soil environment (Zinke effects), could explain the plant identity effects for saprotrophs and other nonsymbiotic groups, as well as for symbiotrophs (Prescott & Grayston, ; Waring et al., ). Host specificity may also play an indirect role via interaction between host‐specific and non‐host‐specific soil microbes (Bakker, Schlatter, Otto‐Hanson, & Kinkel, ).…”
Section: Discussionmentioning
confidence: 99%
“…The formation of “fertile island” by tree/shrub might alter the nutrients, microbial community, and structure of the soil in vertical and horizontal directions (Waring et al, ; Yao et al, ). Our study showed that SOC, TN, TP, BD, SWC, and pH presented a strong spatial heterogeneity.…”
Section: Discussionmentioning
confidence: 99%
“…McCormick and Gibble 2014), and the effects of plants on the trace element chemistry of the soils in which they grow (e.g. Waring et al 2015). Either could be a mechanism for locally positive intraspecific plant-soil feedback that could help maintain high environmental heterogeneity, with potential but complex implications for biodiversity (van der Putten et al 2013; Yang et al 2015).…”
Section: Discussionmentioning
confidence: 99%